Analisis Ayat-Ayat Tentang Belajar Mengajar - Marsya Al-Farin; Najiha Azzahra; Nurul Aini; Zaky Raihan; Wismanto Wismanto (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
Seeking knowledge is an obligation for humans, men and women, young and old, adults and children, in ways appropriate to their circumstances, talents and abilities. So on this occasion the author will discuss some verses about teaching and learning. The purpose of writing this article is to find out the verses that command us to learn and teach. This research uses a qualitative method with a literature review approach regarding teaching and learning verses. Here, we, the authors, try to discuss verses from the Koran about teaching and learning. The research results of verses about teaching and learning: QS. Al-Alaq verses 1-5 contain the command to read as motivation in seeking knowledge, QS. An-Nahl verse 78 Allah grants hearing with which humans are able to hear, sight with which humans are able to see various things, and a heart with which humans are able to find their identity and holiness in the form of reason whose center is the heart. And QS. Luqman verses 17-19 commands to perform prayers, be patient, not be arrogant and the story of Luqman Al-Hakim is a portrait of parents educating their children through teaching.